Day-Case Laparoscopic Cholecystectomy: A Single-Center Experience from Benghazi Medical Center - Eldurssi, Omar; Moftah, Mohmed (AlQalam Journal of Medical and Applied Sciences, 2026)
Day-case laparoscopic cholecystectomy (LC) is widely recognized as a safe and cost-effective treatment for symptomatic gallstone disease. Advances in minimally invasive surgery, anesthesia, and perioperative care have facilitated early discharge without increasing postoperative morbidity. This study evaluated the feasibility, safety, and clinical outcomes of day-case laparoscopic cholecystectomy at Benghazi Medical Center, Benghazi, Libya. A retrospective cross-sectional study was conducted between January 2021 and December 2022 and included 315 patients who underwent elective laparoscopic cholecystectomy for symptomatic cholelithiasis. Patients with complicated gallstone disease, emergency procedures, or concomitant surgeries were excluded. Demographic data, comorbidities, operative findings, postoperative outcomes, length of hospital stay (LOS), and readmission rates were analyzed. Patients were grouped according to hospital stay (≤24 hours and >24 hours). Statistical analysis was performed using SPSS version 25, with P < 0.05 considered statistically significant. The median age was 38 years (IQR 20–50), and 91.7% of patients were female. Most patients (87%) had no significant comorbidities. The mean postoperative LOS was 1.2 ± 0.57 days. Twenty-three patients (7.3%) were discharged on the same day, and 231 (73.3%) were discharged within 24 hours. Conversion to open surgery occurred in 4.1% of cases. The overall complication rate was low, and the readmission rate was 1.6%. Drain placement was significantly associated with prolonged hospital stay (P < 0.001), while other demographic and clinical variables showed no significant association. Day-case laparoscopic cholecystectomy at Benghazi Medical Center is feasible and safe. With proper patient selection and optimized perioperative management, early discharge can be achieved with low complication and readmission rates.